Vitamin D and Exercise Are Major Determinants of Natural Killer Cell Activity, Which Is Age- and Gender-Specific - Oh, Sooyeon; Chun, Sukyung; Hwang, Sena; Kim, Jongseok; Cho, Yuri; Lee, Jooho; Kwack, KyuBum; Choi, Sang-Woon (Frontiers in Immunology, 2021)
Background: Vitamin D plays a potential role in preventing or ameliorating the severity of COVID-19. Natural killer (NK) cells mediate early immune responses to COVID-19. Objective: The aim was to investigate whether vitamin D affected NK cell activity (NKA) and whether NKA could be influenced by lifestyle factors. Methods: This was a cross-sectional association study using health check-up and NKA data of 2,095 subjects collected from 2016 to 2018 in a health check-up center in the Republic of Korea. Individuals with malignant or inflammatory diseases were excluded. NKA was measured using the interferon-γ (IFN-γ) stimulation method. The association of NKA with 25-(OH)-vitamin D (25(OH)D) and other factors was investigated by multiple logistic regression analysis. Results: The average age of subjects was 48.8 ± 11.6 years (52.9% of subjects were female) and the average NKA was 1,243 ± 1,044 pg/mL. Compared to the 25(OH)D level < 20 ng/mL, the 25(OH)D level 30–39.9 ng/mL significantly decreased the risk of very low NKA (< 100 pg IFN-γ/mL) (OR: 0.557; 95% CI: 0.315, 0.984; P = 0.044). The same association was observed in men (OR: 0.358; 95% CI: 0.138, 0.929; P = 0.035) but not in women. For age ≤ 60, the 25(OH)D level 30–39.9 ng/mL significantly decreased the risk of very low NKA (OR: 0.496; 95% CI: 0.246, 0.999; P = 0.050). Age was associated with the risk of very low NKA in men but not in women. Exercise reduced the risk in women but not in men. For age > 60, exercise decreased the risk significantly (P = 0.001). Conclusion: Vitamin D was associated with NK cell immunity upon adjustment for multiple factors. There were gender- and age-dependent differences in factors that influenced NKA. Exercise and vitamin D are major factors affecting NKA.